Development of internet-based remote laboratory for PID control experiments - Abdul Wahab, Hanani (2007)
In control engineering education, concepts taught through lectures are often complemented by practical laboratory experimentation. However, many controlengineering classes do not include a lab component because of significant expense, space and time considerations. As a result, an interactive experiment with real world systems and equipments needs to improve the motivation of control engineering students and develop an engineering approach to solve practical problems. The Interlab project was initiated in November 2005 at International Islamic University of Malaysia. The aim of the thesis is to develop technologies that enable laboratory equipment to be controlled remotely by students through the Internet. This thesis involved design and development of lab scale missile launcher model, modeling and parameters identification of the plant, design and implementation of PID controller and development of website for remote control laboratory for control experimentation. The laboratory uses a NetMeeting; a streaming server to broadcast live video of the plant. When students do their experiment online, they would get instant feedback of their control action by observing movements of the equipment from the video. This would give students a better feel of the laboratory. Students can perform laboratory experiment on the plant using xPC Target Web Browser Interface from any computer connected to the Internet. The initial result shows that the proposed system worked as expected. The use of laboratory equipment would be optimized and students learning experience would also be enhanced.